PENGEMBANGAN E-BOOK INTERAKTIF BERBASIS RADEC UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN SURYODININGRATAN 3 - Tri Budi Utami; Henry Aditia Rigianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop an interactive e-book based on the RADEC (Read, Answer, Discuss, Explain, and Create) learning model to improve mathematics learning outcomes for fourth-grade elementary school students. This study used a Research and Development (R&D) approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were fourth-grade students from SD Negeri Suryodiningratan 3 and SD Negeri Lempuyangan 1, Yogyakarta. The research instruments consisted of expert validation sheets, teacher and student response questionnaires, and learning achievement tests (pretest and posttest). The results showed that the RADEC-based interactive e-book was categorized as highly feasible, with a validation score of 92.5% from material experts and 96% from media experts. The practicality test obtained a teacher response score of 84.4%, student responses of 89.6% in limited trials, and 90.1% in wider implementation, all classified as very good. The effectiveness test using the paired sample t-test indicated a significance value (Sig. 2-tailed) < 0.05, proving a significant improvement in students’ learning outcomes after using the e-book.Therefore, the interactive e-book based on the RADEC model is proven to be feasible, practical, and effective in improving mathematics learning outcomes for elementary students. This media also serves as a digital learning innovation that supports the Merdeka Curriculum and aligns with the characteristics of Generation Alpha, who are closely associated with technology.